Effectiveness of color in Gen Z's decision-making for confectionery brands on social media / Siti Zulaikha Abdul Aziz Zaiddi and Zuhaili Akmal Ismail - Abdul Aziz Zaiddi, Siti Zulaikha; Akmal Ismail, Zuhaili (Faculty of Art and Design, 2023)
Colour plays a crucial role in the advertising industry as it can influence consumers' emotions, attitudes, and purchasing decisions. In the case of a Malaysia confectionery brand's advertisement on Instagram, colour can be used strategically to appeal to the target audience and convey the desired message effectively. This research identifies the role of colours that contributes to consumers' purchasing decisions and evaluates the effectiveness of the colour in enhancing the brand's presence on social media. A questionnaire was used as the primary research tool to collect data from sixty selected respondents based on their Instagram usage and familiarity with the confectionery brand. The questionnaire consisted of open-ended and closed-ended questions designed to include respondents' attitudes, emotions, and behaviours towards colour in the advertisement. The findings which incorporate quantitative and thematic analysis, show a relationship between colour influencing consumers' attitudes, emotions, and purchasing decisions. The following colours, red and yellow, were ranked as the most influential colours in consumers' attitudes, emotions, and purchasing decisions on Instagram. Brown, black and white were classified as the least significant colours. These findings are valuable implications for brand strategists operating in the Malaysian confectionery industry. By understanding the effectiveness of different colour schemes and the emotions and attitudes that different colours evoke in consumers on Instagram, brand strategists can make informed decisions to enhance their brand's presence and impact on social media. This research contributes to the body of knowledge on the role of colour in advertising and provides practical insights for brand strategists seeking to optimise their social media campaigns on platforms like Instagram.